Politeness Strategies Of Inviting Utterances By English Department Students Of Muhammadiyah University Of Surakarta - Nuraini, Sholihah Dwi, Dra. Siti Zuhriah Ariatmi, M. Hum (2017)
This research focuses on invitation strategies and politeness strategies used by English Department students. The data of this research are inviting utterances made by the students of the first semester of English Department of Muhammadiyah University of Surakarta. The data sources are the documents which consist of utterances of students' answer. The researcher collects the data by using DCT (Discourse Completion Task). The DCT contains the script dialog that shows various scenarios. To analyze invitation strategies the researcher adopted strategies of Suketi (2014), while to analyze politeness strategies the researcher uses the theory of Brown and Levinson (1978). The result shows that (1) there are fourteen strategies of invitation used by English Department students and (2) there are four strategies of politeness used by English Department students. The fourteenth strategies of invitation are performative strategy, asking for willingness strategy, want strategy, imperative strategy, hoping strategy, and the others strategy are the combination of asking for willingness plus hoping strategy, asking for willingness plus imperative strategy, hoping plus asking for willingness strategy, imperative plus hoping strategy, performative plus asking for willingness strategy, performative plus hoping strategy, want plus asking for willingness strategy, want plus hoping strategy, and want plus performative strategy. Meanwhile, most of the students usually use the strategy of asking for willingness, because this strategy is used to get definite answer from the hearer; and the fourth strategies of politeness are bald-on record strategy, off record strategy, positive politeness strategy, and negative politeness strategy. Here, the most dominant strategy is negative politeness, because this strategy is indicated by lengthening the distance. It emphasizes the hearers' right to freedom and can be seen as a deference strategy.